Analysis of Nucleotide Alterations in the E6 Genomic Region of Human Papillomavirus Types 6 and 11 in Condyloma Acuminatum Samples from Brazil. (2nd May 2019) - Dias, Marina Carrara; Stuqui, Bruna; Provazzi, Paola Jocelan Scarin; Bittar, Cíntia; Candido, Natália Maria; Matos, Renata Prandini Adum de; Badial, Rodolfo Miglioli; Bonfim, Caroline Measso do; Melli, Patricia Pereira dos Santos; Quintana, Silvana Maria; Cordeiro, José Antônio; Rahal, Paula; et al.
Abstract : Condyloma acuminata (CA), or genital warts, are benign proliferative epidermal or mucous lesions that are caused by infection with human papillomavirus (HPV), mainly the low-risk types 6 and 11. HPV variants are defined as viral sequences that share identity in the nucleotide sequence of the L1 gene greater than 98%. Based on this criterion, HPV6 and 11 variant lineages have been studied, and there are ongoing attempts to correlate these genetic variants with different clinical findings of infection. Therefore, the aims of this study were to detect variants and nucleotide alterations present in the E6 regions of HPV types 6 and 11 found in CA samples, to correlate the HPV presence with the clinical-pathological data of the patients, and to determine phylogenetic relationships with variants from other places in the world. The E6 regions of 25 HPV6 samples and 7 HPV11 samples from CA were amplified using PCR with specific primers. The products were ligated to a cloning vector and five colonies of each sample were sequenced to observe the nucleotide alterations. Twelve samples were identified as the HPV6B3 variant, presenting the mutation (guanine) G474A (adenine), and one of them also showed the mutation (thymine) T369G. The other 13 patients were positive for HPV6B1 without nucleotide alterations. In the analysis of the HPV11 samples, all patients showed the mutations T137C and (cytosine) C380T. One patient also presented the nucleotide alteration T410C. None of the mutations found in the 32 analyzed samples resulted in amino acid changes. Patient age, local occurrence, and HIV infection did not show significant association with HPV infection. Besides, the data found in this study did not show a relationship with the geographical region of isolation when compared to other data from different regions of the world. In this way, despite the nucleotide alterations found, it was not possible to observe amino acid changes and variants grouping according to geographical region.